Credit card use after the final mortgage payment: does the magnitude of income shocks matter? - Barry Scholnick (European Central Bank (ECB), 2009)
We test the hypothesis that consumption smoothing occurs after large, but not small, expected future income shocks. Even though this hypothesis has often been discussed, formal evidence in support of it is rare. We use individual level, monthly, bank account data to examine how expected income shocks from final mortgage payments impact credit card consumption, and the repayment of credit card debt. Our data allows us to identify the exact magnitude and date of final mortgage payments, and also to exploit the random timing of these expected income shocks across individuals. Our results are consistent with the magnitude hypothesis.
Keywords: 330; credit card; final mortgage payment; income shocks; monthly mortgage account; Einkommenshypothese; Kredittilgung; Kreditkarte; Mikrodaten; Kanada